Juvenile xanthogranuloma associated with hypotrophy of the affected arm. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
An 8-day-old baby was first observed due to a 5x4 cm sessile plaque, localized on the left arm, which was present since birth (Fig. 1). It was pink with a yellowish shade and with a hard fibrous consistency. Several diagnoses were hypothesized, favoring the diagnosis of juvenile xanthogranuloma. A skin biopsy was carried out and the histological examination (Fig. 4 and box) confirmed the clinical diagnosis of juvenile xanthogranuloma. In the subsequent months other smaller lesions appeared close to the first one, the scales regressed and the yellowish color got much more evident (Fig. 2). At the age of 4 months, his mother noted that the left arm was significantly smaller than the right arm (Fig. 3). There was a reduction of the dermis and subcutaneous fat, making the dermal vessels more evident.